The Greater Chaco Landscape Ancestors, Scholarship, and Advocacy - Van Dyke, Ruth M.; Heitman, Carrie C. (University Press of Colorado, 2021)
Since the mid-1970s, government agencies, scholars, tribes, and private industries have attempted to navigate potential conflicts involving energy development, Chacoan archaeological study, and preservation across the San Juan Basin. The Greater Chaco Landscape examines both the imminent threat posed by energy extraction and new ways of understanding Chaco Canyon⁠ and Chaco-era great houses and associated communities from southeast Utah to west-central New Mexico in the context of landscape archaeology. Contributors analyze many different dimensions of the Chacoan landscape and present the most effective, innovative, and respectful means of studying them, focusing on the significance of thousand-year-old farming practices; connections between early great houses outside the canyon and the rise of power inside it; changes to Chaco's roads over time as observed in aerial imagery; rock art throughout the greater Chaco area; respectful methods of examining shrines, crescents, herraduras, stone circles, cairns, and other landscape features in collaboration with Indigenous colleagues; sensory experiences of ancient Chacoans via study of the sightlines and soundscapes of several outlier communities; and current legal, technical, and administrative challenges and options concerning preservation of the landscape. An unusually innovative and timely volume that will be available both in print and online, with the online edition incorporating video chapters presented by Acoma, Diné, Zuni, and Hopi cultural experts filmed on location in Chaco Canyon, The Greater Chaco Landscape is a creative collaboration with Native voices that will be a case study for archaeologists and others working on heritage management issues across the globe. It will be of interest to archaeologists specializing in Chaco and the Southwest, interested in remote sensing and geophysical landscape-level investigations, and working on landscape preservation and phenomenological investigations such as viewscapes and soundscapes. Contributors: R. Kyle Bocinsky, G. B. Cornucopia, Timothy de Smet, Sean Field, Richard A. Friedman, Dennis Gilpin, Presley Haskie, Tristan Joe, Stephen H. Lekson, Thomas Lincoln, Michael P. Marshall, Terrance Outah, Georgiana Pongyesva, Curtis Quam, Paul F. Reed, Octavius Seowtewa, Anna Sofaer, Julian Thomas, William B. Tsosie Jr., Phillip Tuwaletstiwa, Ernest M. Vallo Jr., Carla R. Van West, Ronald Wadsworth, Robert S. Weiner, Thomas C. Windes, Denise Yazzie, Eurick Yazzie